Efisiensi Aplikasi SRIKANDI (Sistem Informasi Kearsipan Dinamis Terintegrasi) Pada Asisten Deputi Olahraga Pendidikan Kementrian Pemuda dan Olahraga - Ardiani, Naila Rizka; Febriantin, Kariena; Yulyana, Eka (Program Studi Ilmu Pemerintahan, 2025)
Records management at the Educational Sports Unit of the Ministry of Youth and Sports faces various challenges, such as inefficient manual systems, disruptions due to cyberattacks on the national data center, unexpected maintenance, and mandatory weekly password changes that hinder employee performance. The SRIKANDI application (Integrated Dynamic Archival Information System) is a digital records management system designed by the government to improve the efficiency of electronic archive management. This study employs a qualitative approach to analyze the efficiency of SRIKANDI’s implementation based on the efficiency theory proposed by Sedarmayanti, which includes timeliness, work productivity, work quality, resource utilization, and cost accuracy. The findings indicate that SRIKANDI has been reasonably efficient in supporting records management but still faces several challenges that impede the full optimization of its performance. Academically, this study enriches the literature on the implementation of digital records management systems in the public sector and provides a theoretical foundation for future research on digital transformation in government institutions. Practically, the findings serve as a basis for government agencies to improve records management through technical enhancements, infrastructure strengthening, and data security policies. The public policy implication of this study highlights the need for more adaptive regulations to address cybersecurity risks and the allocation of dedicated budgets for the sustainable maintenance of digital records management systems.